Insights into the effects of Friedreich ataxia on the left ventricle using T1 mapping and late gadolinium enhancement. - Roger E Peverill; Kimberly Y Lin; Mark A Fogel; Michael M H Cheung; W Stuart Moir; Louise A Corben; Glenn Cahoon; Martin B Delatycki (PLoS ONE, 2024)
Background The left ventricular (LV) changes which occur in Friedreich ataxia (FRDA) are incompletely understood. Methods Cardiac magnetic resonance (CMR) imaging was performed using a 1.5T scanner in subjects with FRDA who are homozygous for an expansion of an intron 1 GAA repeat in the FXN gene. Standard measurements were performed of LV mass (LVM), LV end-diastolic volume (LVEDV) and LV ejection fraction (LVEF). Native T1 relaxation time and the extracellular volume fraction (ECV) were utilised as markers of left ventricular (LV) diffuse myocardial fibrosis and late gadolinium enhancement (LGE) was utilised as a marker of LV replacement fibrosis. FRDA genetic severity was assessed using the shorter FXN GAA repeat length (GAA1). Results There were 93 subjects with FRDA (63 adults, 30 children, 54% males), 9 of whom had a reduced LVEF (<55%). A LVEDV below the normal range was present in 39%, a LVM above the normal range in 22%, and an increased LVM/LVEDV ratio in 89% subjects. In adults with a normal LVEF, there was an independent positive correlation of LVM with GAA1, and a negative correlation with age, but no similar relationships were seen in children. GAA1 was positively correlated with native T1 time in both adults and children, and with ECV in adults, all these associations independent of LVM and LVEDV. LGE was present in 21% of subjects, including both adults and children, and subjects with and without a reduced LVEF. None of GAA1, LVM or LVEDV were predictors of LGE. Conclusion An association between diffuse interstitial LV myocardial fibrosis and genetic severity in FRDA was present independently of FRDA-related LV structural changes. Localised replacement fibrosis was found in a minority of subjects with FRDA and was not associated with LV structural change or FRDA genetic severity in subjects with a normal LVEF.